2021
DOI: 10.3389/fonc.2020.596677
|View full text |Cite
|
Sign up to set email alerts
|

Re-Emergence of Minimal Residual Disease Detected by Flow Cytometry Predicts an Adverse Outcome in Pediatric Acute Lymphoblastic Leukemia

Abstract: PurposeWhile the role of minimal residual disease (MRD) assessment and the significance of achieving an MRD-negative status during treatment have been evaluated in previous studies, there is limited evidence on the significance of MRD re-emergence without morphological relapse in acute lymphoblastic leukemia (ALL). We sought to determine the clinical significance of MRD re-emergence in pediatric ALL patients.MethodsBetween 2005 and 2017, this study recruited 1126 consecutive patients newly diagnosed with ALL. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…In 37 children >1-year old with KMT2A + B-cell ALL in CR1, hHSCT using the Beijing Protocol has been shown to improve LFS (89.5 % vs. 52.2 %, respectively, p < 0.001) and reduce CIR (5.3 % vs. 74.1 %, respectively; p < 0.001) compared with no HSCT (64). In 150 paediatric patients who had minimal-residual disease (MRD) recurrence (≥0.01%), Wang et al demonstrated that hHSCT using the Beijing Protocol resulted in a lower 2-year CIR (23.3% vs. 64.0%, respectively; p < 0.001) and a higher OS rate (88.7% vs. 46.3%, respectively; p < 0.001) than did chemotherapy (65). Xu et al reported that 48 children with high-risk T-cell ALL who received hHSCT using the Beijing Protocol during CR1 exhibited higher LFS (65.7% vs. 26.0%, respectively; p = 0.008) and a lower relapse rate (19.8% vs. 56.7%, respectively; p = 0.014) than did patients transplanted when not in CR1, indicating that paediatric patients with T-cell ALL in CR1 benefit from HSCT (66).…”
Section: The Beijing Protocolmentioning
confidence: 99%
“…In 37 children >1-year old with KMT2A + B-cell ALL in CR1, hHSCT using the Beijing Protocol has been shown to improve LFS (89.5 % vs. 52.2 %, respectively, p < 0.001) and reduce CIR (5.3 % vs. 74.1 %, respectively; p < 0.001) compared with no HSCT (64). In 150 paediatric patients who had minimal-residual disease (MRD) recurrence (≥0.01%), Wang et al demonstrated that hHSCT using the Beijing Protocol resulted in a lower 2-year CIR (23.3% vs. 64.0%, respectively; p < 0.001) and a higher OS rate (88.7% vs. 46.3%, respectively; p < 0.001) than did chemotherapy (65). Xu et al reported that 48 children with high-risk T-cell ALL who received hHSCT using the Beijing Protocol during CR1 exhibited higher LFS (65.7% vs. 26.0%, respectively; p = 0.008) and a lower relapse rate (19.8% vs. 56.7%, respectively; p = 0.014) than did patients transplanted when not in CR1, indicating that paediatric patients with T-cell ALL in CR1 benefit from HSCT (66).…”
Section: The Beijing Protocolmentioning
confidence: 99%
“…34 Additionally, three studies demonstrated a correlation between the reemerging of MRD during intensification treatment in patients in CR and the occurrence of relapse. [35][36][37] In conclusion, the highly selected small group of HR patients have a relatively high survival rate of 79% with HR blocks (for some patients followed by SCT). Survival seems favorable compared with other studies reported in literature.…”
Section: Discussionmentioning
confidence: 85%
“…A study of 110 HR patients with a median of five MRD measurements after day 78, showed significant higher occurrence of relapse in patients with high MRD levels at one of more time points compared with patients with low or without quantifiable MRD levels 34 . Additionally, three studies demonstrated a correlation between the reemerging of MRD during intensification treatment in patients in CR and the occurrence of relapse 35–37 …”
Section: Discussionmentioning
confidence: 99%
“…The entire treatment cycle consisted of induction therapy, consolidation therapy, reinduction therapy interspersed with consolidation therapy, and maintenance therapy. The details of the protocol are presented in our previous reports ( 8 , 10 ).…”
Section: Methodsmentioning
confidence: 99%